Meta-analysis of current chemotherapy regimens in advanced pancreatic cancer to prolong survival and reduce treatment-associated toxicities - Chen, Jie (Mol Med Rep, 2019)
Unresectable advanced pancreatic cancer (APC) is a highly lethal malignancy. Although numerous chemotherapeutic regimens are available, evidence regarding the survival extension, the life quality improvement, the associated risks and occurrence rates of adverse effects, is required. The effects of 19 chemotherapy regimens on survival and treatment-associated toxicities in the context of APC treatment were comparatively assessed. A total of 23 randomized controlled trials were included in this network meta-analysis. For overall survival, five regimens, Gemcitabine (Gem)+radiotherapy (Radio), Gem+cisplatin (Cis), Gem+erlotinib (Erl)+bevacizumab (Bev), Gem+capecitabine (Cap)+Erl, and Gem+exatecan, were the most effective treatments, according to their respective high surface under the cumulative ranking (SUCRA) probabilities. Regarding the progression-free survival, five regimens, including Gem+Radio, Gem+Erl+Bev, Gem+Cis, Gem+Cap+Erl and Gem+pemetrexed, were the most effective treatments based on their SUCRA probabilities. Each regimen exhibited advantages and disadvantages, and 14 common treatment-associated toxicities were present in different proportions. The three principal toxic effects included haematological, gastrointestinal and constitutional symptoms. To improve survival, chemotherapy regimens with high SUCRA probabilities require prioritizing. Although treatment-associated toxicities are unavoidable, the regimens presented toxicities in distinct proportions. Therefore, clinicians should assess the disease status of the patients, and balance the benefits and risks of the selected treatment.